Observation of ozone and aerosols in the Antarctic ozone hole of 1991 under the Polar Patrol Balloon (PPB) Project. Preliminary result - Kondo, Yutaka; Murata, Isao; Kanzawa, Hiroshi; Hayashi, Masahiko; Iwasaka, Yasunobu (1994)
We present preliminary results for the PPB (Polar Patrol Balloon) experiment. The balloon was launched at 07:55 UT on 23 September and dropped at 21 UT on 28 September 1991. During the period, ozone and aerosol concentrations were measured correspondingly along the track. During the Lagrangian type observation, drastic change of ozone concentration in 'same air mass' and positive correlation between ozone concentration and sulfate aerosol amount were obtained at the level within 80-78 hPa. During the descent motion at 80 deg S active PSC's (type-1 and -2) were observed from 200 hPa to 80 hPa.